The Effect of Water Activity and Food Consumption on Psychosocial Disorder and Anthropometric Stunting Toddlers - Muslimawati, Ananda Dwi; Noordia, Anna; Yuliastrid, Dita; Mustar, Yetty Septiani (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
are many ways to overcome and reduce the occurrence of stunting. One of them is doing water activities. The aim of this research is to find out whether there is an influence of water activities and food consumption on psychosocial disorders and anthropometry of stunted toddlers. This research used a one group pre-test and post-test design with a sample size of 7 toddlers and sampling used purposive sampling. Height and weight measurements were taken before and after water activities. Meanwhile, to look at food consumption and psychosocial disorders, the data collection technique is in the form of a questionnaire. The results of the study showed that anthropometric values ​​between height and weight had increased compared to psychosocial disorder values. Apart from that, there is a significant difference between the pretest and posttest height of stunted toddlers. The significance value for pretest height is 0.430 and posttest is 0.437 (Sig. >0.05). Then it was also proven by the Paired Sample T-test of 0.029 (Sig. <0.05), this means that there is a difference between pretest and posttest body height. Meanwhile, for body weight and psychosocial disorders, the pretest and posttest did not prove to be a significant difference. Apart from that, water activities can increase appetite. In this study, all toddlers were not identified as having any psychosocial disorders. However, the reality in the field is that there are still stunted toddlers who are afraid of doing water activities or getting introduced to water. Further studies regarding implementation and better measurement procedures are needed in future research.